NOVEL ANTI-DEPRESSANT FAST DISSOLVING TABLET:DESIGN AND DEVELOPME - DESHPANDE TANVEE; KHABALE RAHUL (International Journal of Pharma and Bio Sciences, 2013)
The purpose of the present investigation is to formulate taste masked fast dissolving tablets of venlafaxine hydrochloride, a novel antidepressant, by wet granulation method. Nine formulations were prepared using sodium starch glycolate, croscarmellose sodium and crospovidone as superdisintegrants in different concentrations of 5%, 7.5% and 10%.ingredients like peppermint oil, menthol and sucralose aided in the taste masking process of the drug. The prepared batches were then evaluated for various physical and chemical attributes. Amongst the nine formulations CP-3 emerged as an overall the best formulation showing release profile of almost 100%. Accelerated stability studies were conducted for this batch at 40±2oC and 75±5% RH for one month period.